Trabalhar Além-Fronteiras: O contrato individual de trabalho internacional (De Legibus - Law Journal, 2022)
This text describes and analyses the legal framework and the criterion set by the case law of the Court of Justice of the Union and the national Portuguese courts, concerning the jurisdiction, the applicable law and recognition regimes in the international (individual) employment contract.Recognized, and listed, the advantages of the convergence of competence criterion and those of determining the applicable law (forum and ius), in order to ensure an adequate level of protection to the employee, its distortion, in face of some of the connection factors held in the Court of Justice rulings, is emphasized.
Keywords: nternational (individual) employment contract; International jurisdiction; Applicable law; 1968 Brussels Convention on jurisdiction and the enforcement of judgments in civil and commercial matters; 1980 Rome Convention on the law applicable to contractual obligations; Council Regulation (EC) n.º 44/2001; Regulation (EU) n.º 1215/2012; Regulation (EC) n.º 593/2018; case law of the Court of Justice of the European Union.